2021
DOI: 10.1136/rapm-2021-103161
|View full text |Cite
|
Sign up to set email alerts
|

Recent cannabis use and nightly sleep duration in adults: a population analysis of the NHANES from 2005 to 2018

Abstract: BackgroundWhile popularly consumed for its perceived benefits as a sleeping aid, the impact of cannabis on sleep-wake regulation in clinical studies is inconclusive. The purpose of this study was to determine the relationship between cannabis use and nightly sleep duration in a nationally representative dataset.MethodsA cross-sectional analysis of adults was undertaken using the National Health and Nutrition Examination Survey data from 2005 to 2018. Respondents were dichotomized as recent users or non-users i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Marijuana use has been reported to be associated with either a short or long sleep duration in previous studies ( Babson et al, 2017 , Bhagavan et al, 2020 , Pupko, 2018 , Schwenk et al, 2022 ) and is sometimes perceived as providing benefits as a sleep aid ( Goodhines et al, 2019 , Doremus et al, 2019 , Diep et al, 2022 , Drazdowski et al, 2021 ), which served as a double-edged sword. Schwenk et al found that recent cannabis users had greater adjusted odds of reporting both short and long sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marijuana use has been reported to be associated with either a short or long sleep duration in previous studies ( Babson et al, 2017 , Bhagavan et al, 2020 , Pupko, 2018 , Schwenk et al, 2022 ) and is sometimes perceived as providing benefits as a sleep aid ( Goodhines et al, 2019 , Doremus et al, 2019 , Diep et al, 2022 , Drazdowski et al, 2021 ), which served as a double-edged sword. Schwenk et al found that recent cannabis users had greater adjusted odds of reporting both short and long sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy users, those who were using cannabis for at least 20 of the past 30 days, were even more likely to report sleep durations at the extreme ends of the range ( Schwenk et al, 2022 ). From a sample representing approximately 146 million adults in the U.S., recent cannabis use was associated with the extremes of nightly sleep duration, with suggestions of a dose–response relationship ( Diep et al, 2022 ). In our study, we did not observe a significant association between marijuana or e-cigarette single use and short or long sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…CBD can be used to improve insomnia and anxiety due to its sedating properties at the 5-HT1A receptor with minimal/no detrimental adverse effects [19]. However, recent cannabis users have reported shorter sleep duration than nonusers [20]. And, in individuals identified as repeated cannabis users, increased sleep onset, decreased total sleep time and greater sleep disruption have been described [21].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Sleep disturbances are one of the most common complaints in substance use disorder treatment, 1,2 and there is substantial comorbidity between substance use disorders (SUD) and sleep disorders 3,4 . Attempting to quit substances and the consequent cravings and withdrawal are often associated with sleep disturbances, and these sleep deficits can in turn be reciprocally linked to substance use relapse 5 .…”
Section: Introductionmentioning
confidence: 99%